PENINGKATAN KETERAMPILAN PASSING BAWAH BOLA VOLI MELALUI STRATEGI PEMBELAJARAN SESAMA TEMAN PADA SISWA KELAS IV SD NEGERI 001 EMPAT BALAI KECAMATAN KUOK KABUPATEN KAMPAR - Ernailis Ernailis (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
The background of this study were (1) the majority of students are reluctant to play volleyball because it is difficult to play; (2) in playing volleyball, there are still many students who are not yet using the basic motion correctly; and (3) most of the students have not been able to do down in the passing game of volleyball so that students passing the ball difficult to be directed to his friend. This study aims to determine the learning outcome passing down using peer teaching learning strategi students class IV of SD Negeri 001 Empat Balai Kecamatan Kampar Kuok. The research was conducted in the students class IV of SD Negeri 001 Empat Balai, Kecamatan Kuok, Kampar. The study was conducted over four months, from January 2015 to April 2015. This form of research is classroom action research. The research instrument consists of instruments and instrument performance data collection activity observation sheet form teacher and student activity. Based on the results of research and discussion that the basic motor skills of passing under the students class IV of of SD Negeri 001 Empat Balai, Kecamatan Kuok, Kabupaten Kampar could be enhanced through learning strategies among friends. This statement is supported by the results that have been raised previously, namely: (1) the results of initial tests students' abilities before the application of learning strategies neighbor is 64.7 or category fairly competent; (2) in the first cycle of average ability of students increased by a competent value category (71.1); (3) in the second cycle of average ability students categorized competent (77.1) with 80% completeness. This indicates that the completeness kasikal has been reached, in which the research is successful if the completeness achieved 80% of students scored at least 70.